A Paradigm for Active Database Management Systems (International Journal of Engineering and Computer Science, 2017)
Active database systems support mechanisms that enable them to respond automatically to events that aretaking place either inside or outside the databasesystem itself. Considerable effort has been directed towards improving understanding of such systems inrecent years, and many different proposals have been made and applications suggested. This high level ofactivity has not yielded a single agreed-upon standard approach to the integration of active functionalitywith conventional database systems, but has led to improved understanding of active behaviour descriptionlanguages, execution models, and architectures. This paper presents the fundamental characteristics of activedatabase systems[11], describes a collection of representative systems within a common framework,considers the consequences for implementations of certain design decisions, and discusses tools fordeveloping active applications. Active database management systems are invoked by synchronous eventsgenerated by user or application programs as well as external asynchronous data change events such as achange in sensor value or time. In this paper gives the introduction of active DBMS[12] and discussed howit is different from passive DBMS.